Micro-level evaluation of socio-technological interventions to address climate change-induced stresses in dairy enterprises - Chakravarty, Ritu; Ponnusamy, Kuppusamy; Sendhil, R (Indian Journal of Dairy Science, 2021)
The paper aims at micro-level evaluation of dairy centric socio-technological interventions under the Technology Demonstration Component (TDC) of the National Innovations in Climate Resilient Agriculture (NICRA) Project in Karnal, Yamunanagar and Sirsa districts of Haryana. The interventions were introduced to address the identified climate stresses under the project for enhancing resilience in dairy production. The study was conducted during 2015-16, employing Participatory Rural Appraisal (PRA) techniques to assess the farmers’ feedback on climate change perception and their acceptance and satisfaction of introduced interventions, from the NICRA adopted village in each district. Ten socio-technological interventions were evaluated each based on two dimensions of perceived attributes and benefits sub-evaluation parameters. The reason based satisfaction was recorded on a farmer rating for each intervention. Among six introduced technological interventions, improved fodder crop varieties (total score 28 and 30) and area specific mineral mixture supplementation (total score 28 to 29) were perceived as highly beneficial in terms of sustained milk production even during periods of heat stress followed by moderate beneficial of interventions viz., Vitamin E supplementation, mustard oil supplementation and safe dung disposal through composting. Silage making intervention was perceived as low beneficial (total score 16). The Village Climate Risk Management Committee (VCRMC) was found as a highly beneficial (total score 27 to 30) social intervention, followed by women participation, contingency plan for climate change preparedness in fodder crops and preparation of season-centric milk products as moderate beneficial. The VCRMC was found highest satisfactory as rated by the farmers.